BOOK REVIEWS (Journal of Finance, 1968)
Book reviewed in this article: Critical Essays in Monetary Theory . By S ir J ohn H icks . Essays in Monetary Economics . By H arry G. J ohnson . The Theory of Interest . By F riedrich A. L utz (translated from the second German edition by C. W ittich ). Investment Profit Correlation: A Regression Model of Profits from Common Stock Investments . By W. S cott B auman and T homas A. K lein . Yields on Corporate Debt Directly Placed . By A very B. C ohan . Operations Research Techniques for Capital Investment . By F. H anssmann . Financial Decision‐Making . Edited by E dward J. M ock . Financial Management: Cases and Readings . Edited by P earson H unt and V ictor L. A ndrews . Commercial Financing . Edited by M onroe R. L azere . Public Reporting by Conglomerates: The Issues, the Problems, and Some Possible Solutions . Edited by A lfred R appaport , P eter A. F irmin , and S tephen A. Z eff . Growth, Profitability and Valuation: A Study of United Kingdom Quoted Companies . By A. S ingh and G. W hittington in collaboration with H. T. B urley . American Banking Structure . By G erald C. F ischer . The Machinery of Finance and the Management of Sterling . By A. T. K. G rant . The Merchant Banking Arena . By R ichard K ellett . An Introduction to the Theory of Finance . By B asil J. M oore . The Foundations of Money and Banking . By B oris P. P esek and T homas R. S aving . Capital Movement and Economic Development: Proceedings of a Conference Held by the International Economic Association . Edited by J ohn H. A dler . Trade and Trade Policy for Development . By S taffan B urenstam L inder . Export Instability and Economic Development . By A lasdair I. M acbean . Balance‐of‐Payments Adjustment Policies: Japan, Germany, and the Netherlands . By M ichael M ichaely . Government Finance: Economics of the Public Sector . By J ohn F. D ue .